Association of nitrate ion with metal cations in aqueous solution : a UV-Vis spectrometric and factor-analytical study - Gvozdić, Vlatka; Tomišić, Vladislav; Butorac, Vjekoslav; Simeon, Vladimir (2009)
Summary: Ion association in aqueous solutions of varied concentrations of LiNO3, NaNO3, Ca(NO3)2, Sr(NO3)2, Ba(NO3)2, Mn(NO3)2, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, Zn(NO3)2, and Cd(NO3)2 was studied by means of UV spectrometry. In all cases, except for Zn(NO3)2(aq) the principal-components (PCA) and evolving-factor (EFA) analyses of the spectra indicated formation of associated ion pairs [MNO3]z-1 (Mz denotes the cation) at higher salt concentrations. The (dis)similarities of the [MNO3]z-1 (Mz spectral profiles (computed by EFA) were examined by means of cluster analysis. The influence of transition-metal ions on the nitrate UV spectrum was found to be remarkably different compared to that of non-transition cations. That could be a consequence of different types of cation-anion interactions. The ion pairs containing non-transition metal ions could be regarded as classical electrostatic ones, whereas a weak coordination interaction was presumably present in the ion pairs formed by the nitrate and the cations of transition metals
Bibliografija: 19 jed
Keywords: Asocijacija iona -- Vodena otopina -- UV-Vis spektrometrija -- Analiza glavnih komponenata -- Evolucijska faktorska analiza